2018
DOI: 10.1007/s00431-018-3222-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of resuscitation, respiratory function monitoring data and outcomes in preterm infants

Abstract: Intraventricular haemorrhage (IVH) and bronchopulmonary dysplasia (BPD) are major complications of premature birth. We tested the hypotheses that prematurely born infants who developed an IVH or BPD would have high expiratory tidal volumes (V) (V > 6 ml/kg) and/or low-end tidal carbon dioxide (ETCO) levels (ETCO levels < 4.5 kPa) as recorded by respiratory function monitoring or hyperoxia (oxygen saturation (SaO) > 95%) during resuscitation in the delivery suite. Seventy infants, median gestational age 27 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
2
20
0
1
Order By: Relevance
“…We reviewed the records of infants born at less than or equal to 33 weeks of gestational age who required resuscitation in the delivery suite between March 2010 and March 2014. A certain part of their data was reported in a previous paper [3]. Ethical approval was given by the Outer London Ethics Committee for the data collection.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We reviewed the records of infants born at less than or equal to 33 weeks of gestational age who required resuscitation in the delivery suite between March 2010 and March 2014. A certain part of their data was reported in a previous paper [3]. Ethical approval was given by the Outer London Ethics Committee for the data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, fluctuations of pCO 2 can adversely affect cerebral oxygenation and perfusion and the electrical activity of the brain [6]; such fluctuation is predictive of adverse neurodevelopmental outcomes [7]. We have demonstrated that not only high EtCO 2 levels during resuscitation in the delivery suite were associated with IVH development but also inflations resulting in larger tidal volumes and lower EtCO 2 levels [3]. Those findings were subsequently confirmed by Mian and colleagues who found that tidal volumes in excess of 6 ml/kg were associated with cerebral damage in the neonatal period [8].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations